Silicon-Vacancy Centers in Ultra-Thin Nanocrystalline Diamond Films - Stehlik, Stepan; Ondic, Lukas; Varga, Marian; Fait, Jan; Artemenko, Anna; Glatzel, Thilo; Kromka, Alexander; Rezek, Bohuslav (Micromachines, 2018)
Color centers in diamond have shown excellent potential for applications in quantum information processing, photonics, and biology. Here we report the optoelectronic investigation of shallow silicon vacancy (SiV) color centers in ultra-thin (7⁻40 nm) nanocrystalline diamond (NCD) films with variable surface chemistry. We show that hydrogenated ultra-thin NCD films exhibit no or lowered SiV photoluminescence (PL) and relatively high negative surface photovoltage (SPV) which is ascribed to non-radiative electron transitions from SiV to surface-related traps. Higher SiV PL and low positive SPV of oxidized ultra-thin NCD films indicate an efficient excitation-emission PL process without significant electron escape, yet with some hole trapping in diamond surface states. Decreasing SPV magnitude and increasing SiV PL intensity with thickness, in both cases, is attributed to resonant energy transfer between shallow and bulk SiV. We also demonstrate that thermal treatments (annealing in air or in hydrogen gas), commonly applied to modify the surface chemistry of nanodiamonds, are also applicable to ultra-thin NCD films in terms of tuning their SiV PL and surface chemistry.
Keywords: nanocrystalline diamond; diamond; silicon-vacancy center; color center; Kelvin probe force microscopy; surface photovoltage